Exercise in School Physical Education Increase Bone Mineral Content and Density: Systematic Review and Meta-Analysis - Garcia-Hermoso, A (Taylor and Francis Ltd., 2022)
This systematic review and meta-analysis aimed to evaluate the effectiveness of interventions through Physical Education (PE) exercises on bone mineral content (BMC) and density (BMD) of children and adolescents. The research was conducted using the online electronic databases PubMed, Science Direct, Web of Science and Scopus (March 2021). The analysis was restricted to school-based studies that examined the effect of PE interventions on BMC and BMD in schoolchildren (<18 years old). Standardised mean differences (SMD) with 95% confidence interval (CI) and random-effects models were calculated. The heterogeneity and inconsistency of the studies were estimated using Cochran’s Q-statistic and I 2, respectively. Twenty-two studies with 2,556 participants were selected. PE interventions were associated with a significant increase in BMC (SMD = 1.348; 95% CI, 1.053–1.643) and BMD (SMD = 0.640; 95% CI, 0.417–0.862). Femoral neck subgroup analysis indicate an increase in BMC for boys (SMD = 1.527; 95% CI, 0.990–2.065) and girls (SMD = 1.27; 95% CI, 0.782–1.767), and in BMD for boys (SMD = 0.518; 95% CI, 0.064–0.972) and girls (SMD = 0.817; 95% CI, 0.349–1.284). Finally, increases are reported in the lumbar spine BMC for boys (SMD = 1.860; 95% CI, 1.018–2.700) and girls (SMD = 1.275; 95% CI, 0.782–1.767). This meta-analysis provides insights into the effectiveness of interventions aimed at including physical exercise in PE on bone mass, suggesting that increasing the proportion of curriculum time allocated to PE may improve students’ BMD and BMC, especially in the femoral neck and lumbar spine. © 2021 European College of Sport Science.